2013
DOI: 10.1111/dom.12175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glucagon-like peptide-1 receptor agonists on cardiovascular risk: a meta-analysis of randomized clinical trials

Abstract: The present meta-analysis confirms the cardiovascular safety of GLP-1 RA, at least in the short term and in low-risk individuals. GLP-1 RA could have a beneficial effect on the incidence of MACE, at least in comparison with placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
97
0
5

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 25 publications
6
97
0
5
Order By: Relevance
“…explain early clinical data suggesting improved cardiovascular outcomes in GLP-1 analog-treated patients (16). Second, T2D is associated with increased platelet reactivity and risk of thrombus formation, higher incidences of myocardial infarction and stroke (46), and diminished sensitivity to widely used antiplatelet drugs, such as aspirin and clopidogrel (5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…explain early clinical data suggesting improved cardiovascular outcomes in GLP-1 analog-treated patients (16). Second, T2D is associated with increased platelet reactivity and risk of thrombus formation, higher incidences of myocardial infarction and stroke (46), and diminished sensitivity to widely used antiplatelet drugs, such as aspirin and clopidogrel (5).…”
Section: Discussionmentioning
confidence: 99%
“…The first of those studies examining DPP-4is, namely the SAVOR-TIMI 53, EXAMINE, and TECOS studies, have demonstrated no increase in cardiovascular events (10)(11)(12). By contrast, relatively short-term studies (13)(14)(15)(16), in arguably lower-risk patients treated with GLP-1R agonists and DPP-4i, have suggested beneficial effects on cardiovascular event rates. Because the rather modest and brief improvements in glycemic control observed in these studies are unlikely to explain the observed benefits, we wondered whether GLP-1-targeted therapies may reduce macrovascular event rates in these particular patient populations by directly inhibiting platelet aggregation and thrombus formation.…”
mentioning
confidence: 99%
“…Alogliptin decreased fasting TG, apoB-48, and remnant-like particles (28), and anagliptin reduced fasting TG, apoB, and LDL-C (29). These effects may be related to the efficacy of these therapies in improving glycemic control with both GLP-1R agonists and DPP-4 inhibitors (12,30,31) and in reducing weight that is more notable with GLP-1R agonists than DPP-4 inhibitors (12,32,33). Future studies are required to determine the contribution of weight loss and improved glycemic control to fasting and postprandial lipids and to delineate the effects of these compounds on lipids independent of improved glycemic control and weight loss.…”
Section: Glp-1r Agonists Improve Fasting and Postprandial Lipid Profimentioning
confidence: 95%
“…Several recent meta-analyses indicated modest reductions in fasting LDL-C, total cholesterol, and TG with small or no significant improvement in HDL-C following chronic treatments with GLP-1R agonists (12)(13)(14) or DPP-4 inhibitors (13,15). For example, treatment with exenatide or liraglutide for several weeks to 3 years reduced fasting levels of TG, total cholesterol and LDL-C, increased HDL-C (16)(17)(18)(19); and reduced fasting apoB (19)(20)(21)(22), apoB-48 (a surrogate measure of intestinal lipoprotein particle numbers) (23), and free fatty acid (FFA) (24)(25)(26).…”
Section: Glp-1r Agonists Improve Fasting and Postprandial Lipid Profimentioning
confidence: 99%
“…Recent studies suggest BP-lowering effects of GLP-1RA. [20][21][22][23] In contrast, some [24][25][26] but not all 16 experimental studies showed a rise in BP after GLP-1 injection.…”
mentioning
confidence: 95%